Aktivitas Komunitas Sepeda dalam Gerakan Membangun Budaya Bersepeda di Kota Bandung - Arya Rivandra; Mohamad Subur Drajat (UNISBA Press, 2023)
Abstract. This study aims to see the activities of the bicycle community in the cityof Bandung in the campaign to build a cycling culture. Cycling culture refers to ahabit of using bicycle transportation in their daily lives, there are still many cyclistswho are still not orderly in traffic. The presence of Forkom Bandung Raya is analternative forum in carrying out activities regarding the movement to build acycling culture in the city of Bandung. This study looks at the communication sideof the community who are members of the Forkom Bandung Raya. The grandtheory for this research is social interaction, the interaction here is behavior that iscarried out in groups, so that it has an influence on the environment in accordancewith the goals to be achieved. The method used in this research is a qualitativemethod, with a case study approach. Data collection techniques used are interviews,observation. The informants in this study were the management of the BandungRaya Forkom and several leaders of the bicycle community. The results of thisstudy indicate that there are several factors that support the process of campaignactivities by Forkom Bandung Raya together with the bicycle community in the cityof Bandung. Collaborative activities, both in the planning process and in theimplementation of campaign activities, focus on delivering educational messagesrelated to the cycling movement and building a culture of orderly cycling, both tobicycle users and to the wider community, especially in the city of Bandung.Abstrak. Penelitian ini bertujuan untuk melihat aktivitas komunitas sepeda di KotaBandung dalam kampanye membangun budaya bersepeda. Budaya bersepedamerujuk pada sebuah kebiasaan untuk menggunakan transportasi sepeda dalamkesehariannya, masih banyak pesepeda yang masih belum tertib dalam berlalulintas. Hadirnya Forkom Bandung Raya sebuah forum dalam melakukan aktivitasmengenai gerakan membangun budaya bersepeda di Kota Bandung. Penelitian inimelihat sisi komunikasi yang dilakukan oleh komunitas yang tergabung dalamForkom Bandung Raya. Teori yang menjadi pijakan dalam penelitian ialah interaksisosial, interaksi disini perilaku yang dilakukan secara berkelompok, sehinggamemberikan pengaruh bagi lingkungannya sesuai dengan tujuan yang hendakdicapai. Metode yang digunakan dalam penelitian ini adalah metode kualitatif,dengan pendekatan studi kasus. Teknik pengumpulan data yang digunakan adalahwawancara, observasi. Yang menjadi informan pada penelitian ini KepengurusanForkom Bandung Raya dan beberapa ketua komunitas sepeda. Hasil penelitian inimenunjukan bahwa terdapat bebrapa faktor yang menjadi pendukung dalam proseskegiatan kampanye oleh Forkom Bandung Raya bersamaan dengan komunitassepeda di Kota Bandung. Kegiatan kolaborasi baik itu pada proses perencanaan danpada pelaksanaan kegiatan kampanye ini berfokus pada penyampaian pesan edukasiterkait dengan gerakan bersepeda dan membangun budaya tertib bersepeda baik itukepada para pengguna sepeda maupun kepada masyarakat luas khusnya di KotaBandung.